2020
DOI: 10.1016/j.econlet.2019.108777
|View full text |Cite
|
Sign up to set email alerts
|

What drives Bitcoin’s price crash risk?

Abstract: We examine the association of the Bitcoin price crash risk with economic uncertainty and behavioral factors. We show that economic uncertainty displays a negative and significant association with Bitcoin price crash risk, indicating that when economic uncertainty is high, the crash risk of Bitcoin is low. We also find that behavioral factors have a weak association with Bitcoin crash risk. Our results suggest that investors can hedge economic uncertainty by investing in Bitcoin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…In this paper, we focus on value at risk (VaR) and the related conditional value at risk (CVAR), also referred to as expected shortfall, to measure potential losses in a portfolio over a given time horizon (Conlon and Cotter, 2013). While other measures of crash risk have also been proposed in the context of cryptocurrencies (Kalyvas et al, 2019), the methods detailed here are appropriate for frequently examined horizons of importance to investors.…”
Section: Downside Risk Measurementmentioning
confidence: 99%
“…In this paper, we focus on value at risk (VaR) and the related conditional value at risk (CVAR), also referred to as expected shortfall, to measure potential losses in a portfolio over a given time horizon (Conlon and Cotter, 2013). While other measures of crash risk have also been proposed in the context of cryptocurrencies (Kalyvas et al, 2019), the methods detailed here are appropriate for frequently examined horizons of importance to investors.…”
Section: Downside Risk Measurementmentioning
confidence: 99%
“…Recent studies differ in the econometric methodologies proposed to study the dynamics of the cryptocurrencies and also on the set of factors used to rationalise its behaviour. We highlight important contributions by Ciaian et al (2015), Hayes (2017), Kristoufek (2015), Polasik, Piotrowska, Wisniewski, Kotkowski, and Lightfoot (2015), Zhu, Dickinson, and Li (2017), Blau (2017), Zhang, Wang, Li, and Shen (2018), Bouri, Gupta, Lahiani, and Shahbaz (2018), Jareno, Gonzales, Tolentino, and Sierra (2020) and Kalyvas, Papakyriakou, Sakkas, and Urquhart (2020). These authors use a variety of econometric models such as OLS, VECM, Wavelet Analysis, IV Estimation, GARCH and MF‐DCCA models and consider market and technical variables to explain the dynamics of cryptocurrencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors demonstrated that these cryptocurrencies act as hedge against economic policy risk. In current strand, several studies concluded that cryptocurrencies act as hedge and safe haven (Bouri et al 2017b(Bouri et al , 2017c(Bouri et al , 2017d(Bouri et al , 2020aBouri and Gupta 2019;Chen et al 2021;Cheng and Yen 2020;Colon et al 2021;Fang et al 2020;Fasanya et al 2021;Jiang et al 2021;Kalyvas et al 2020;Koumba et al 2020;Matkovskyy et al 2020 Rubbaniy et al 2021;Wu et al 2019Wu et al , 2021Cheng and Yen 2020;Yen and Cheng 2021). In contrast, cryptocurrencies do not act as hedge or safe-haven for economic policy uncertainty (Cheema et al 2020;Fasanya et al 2021;Hasan et al 2021;Jiang et al 2021;Lucey et al 2021;Wu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Purposefully, our research aims to study the undiscovered phenomena of other cryptocurrencies to ensure whether the losing dominance of Bitcoin (Corbet et al 2018b;Katsiampa et al 2019) in the cryptocurrency market unlocks the abilities of other uppermost cryptocurrencies Bitcoin, Ethereum, XRP, Bitcoin Cash, and Litecoin). (Kalyvas et al 2020) documented the behavioral aspect of Bitcoin investors and Bitcoin price crash uncertainty with economic policy uncertainty. Particularly, the association of Bitcoin price crash risk and economic policy uncertainty demonstrated a strong negative correlation pattern.…”
Section: Role Of Cryptocurrencies For Country Epusmentioning
confidence: 99%
See 1 more Smart Citation